Biomonitoring method for neonicotinoid insecticides in urine of non-toilet-trained children using LC-MS/MS. Issue 2 (1st February 2020) - Ueyama, Jun; Aoi, Arisa; Ueda, Yuko; Oya, Naoko; Sugiura, Yuka; Ito, Yuki; Ebara, Takeshi; Kamijima, Michihiro
ABSTRACT: There is a growing appreciation of the importance of determining chemical exposure levels in early childhood, as well as in embryonic and foetal life, which are now widely believed to be essential for gaining insight into potential health risks associated with these chemicals. To facilitate the assessment of exposure to neonicotinoid insecticides (NEOs) in non-toilet-trained children, a new method using disposable diapers (nappies) was developed for the simultaneous determination of the NEOs acetamiprid and its metabolite N -desmethylacetamiprid, clothianidin, dinotefuran, imidacloprid, thiacloprid, and thiamethoxam (NEO biomarkers). The urine absorbed in disposable diapers was extracted with acetone (diaper urine) and was cleaned using a solid-phase extraction column, before analysis with LC-MS/MS. The absolute recoveries of NEO biomarkers were 19–50%. Good results were observed for the linearity of the matrix-matched calibration curves ( r 2 = 0.983–0.996; concentration range LOQ-20 µg L −1 ) and the precision of intra-day (% relative standard deviation (%RSD): 3.3–12.7%) and inter-day (%RSD: 4.3–19.5%) analyses. The lowest and highest limits of detection of the developed method were 0.07 µg L −1 for acetamiprid and 0.75 µg L −1 for clothianidin. The developed method was applied for the evaluation of fifty diapered three-year-old children in Japan. Importantly, the study revealed relatively high detection rates for dinotefuran and N -desmethylacetamiprid; 84% and 78% respectively. The highest geometric mean of dinotefuran urinary concentration was 2.01 µg L −1 . Thus, a method for determining NEO biomarkers in urine extracted from disposable diapers was established. This is the first report on the simultaneous quantitative analysis of NEO biomarkers of diaper-absorbed urine samples.